Microscopic observation of unworn siloxane-hydrogel soft contact lenses by atomic force microscopy - González-Méijome, José Manuel (2006)
In the present study, samples of lotrafilcon A, balafilcon A, and galyfilcon A contact lenses were observed by atomic force microscopy (AFM) in tapping mode at areas ranging from 0.25 to 400 m2. Mean roughness (Ra), root-mean-square roughness (Rms) and maximum roughness (Rmax) in nanometers were obtained for the three lens materials at different magnifications. The three contact lenses showed significantly different surface topography. However, roughness values were dependent of the surface area to be analyzed. For a 1 m2 area, statistics revealed a significantly more irregular surface of balafilcon A (Ra = 6.44 nm; Rms = 8.30 nm; Rmax = 96.82 nm) compared with lotrafilcon A (Ra = 2.40 nm; Rms = 3.19 nm; Rmax = 40.89 nm) and galyfilcon A (Ra = 1.40 nm; Rms = 1.79 nm; Rmax = 15.33 nm). Ra and Rms were the most consistent parameters, with Rmax presenting more variability for larger surface areas. The higher roughness of balafilcon A is attributed to the plasma oxidation treatment used to improve wettability. Conversely, galyfilcon A displays a smoother surface. Present observations could have implications in clinical aspects of siloxane-hydrogel contact lens wear such as lens spoliation, resistance to bacterial adhesion, or mechanical interaction with the ocular surface.